Aëtiana : the method and intellectual context of a doxographer - Mansfeld, Jaap. (Philosophia Antiqua, 1997)
The theme of this study is the Doxography of problems in physics from the Presocratics to the early first century BCE attributed to Aëtius. Part I focuses on the argument of the compendium as a whole, of its books, of its sequences of chapters, and of individual chapters, against the background of Peripatetic and Stoic methodology. Part II offers the first full reconstruction in a single unified text of Book II, which deals with the cosmos and the heavenly bodies. It is based on extensive analysis of the relevant witnesses and includes listings of numerous doxographical-dialectical parallels in other ancient writings. This new treatment of the evidence supersedes Diels' still dominant source-critical approach, and will prove indispensable for scholars in ancient philosophy.